2019
DOI: 10.1186/s12985-019-1233-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex PCR-based titration (MPBT) assay for determination of infectious titers of the three Sabin strains of live poliovirus vaccine

Abstract: BackgroundConventional assays to titrate polioviruses usually test serial dilutions inoculated into replicate cell cultures to determine a 50% cytopathic endpoint, a process that is both time-consuming and laborious. Such a method is still used to measure potency of live Oral Poliovirus Vaccine during vaccine development and production and in some clinical trials. However, the conventional method is not suited to identify and titrate virus in the large numbers of fecal samples generated during clinical trials.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The results summarized in Table 1 show that qmosRT-PCR was able to specifically identify and quantify each Sabin strain in all possible combinations. Consistent with our previous studies [18,19,21], qmosRT-PCR was found to be very specific for the identification and quantification of the different Sabin strains. To study the growth kinetics of Sabin strains in cells infected with the same virus concentration as used in the neutralization tests, monolayers of HEp-2C cells were prepared in 96-well plates and infected with 100 CCID 50 /per well of a mixture of the three Sabin strains.…”
Section: Mpbn Assay Designsupporting
confidence: 91%
See 1 more Smart Citation
“…The results summarized in Table 1 show that qmosRT-PCR was able to specifically identify and quantify each Sabin strain in all possible combinations. Consistent with our previous studies [18,19,21], qmosRT-PCR was found to be very specific for the identification and quantification of the different Sabin strains. To study the growth kinetics of Sabin strains in cells infected with the same virus concentration as used in the neutralization tests, monolayers of HEp-2C cells were prepared in 96-well plates and infected with 100 CCID 50 /per well of a mixture of the three Sabin strains.…”
Section: Mpbn Assay Designsupporting
confidence: 91%
“…This communication describes the development of a multiplex PCR-based neutralization (MPBN) assay for anti-poliovirus antibodies titration that uses a quantitative multiplex one-step RT-PCR (qmosRT-PCR) [18] as a read-out instead of CPE used in the conventional assay. Recently, we successfully used a similar approach to develop a multiplex PCR-based titration (MPBT) assay for the simultaneous titration of the three poliovirus serotypes [19].…”
Section: Introductionmentioning
confidence: 99%
“…Sabin 2 and the recovered nOPV2c1-295 viruses were titrated by MPBT assay [ 27 ] with small modifications; only primers and probe for poliovirus type 2 were used.…”
Section: Methodsmentioning
confidence: 99%
“…Recent experience with poliovirus diagnostic advances further supports the feasibility of such a sequence of events (e.g. detection of emerging vaccine-related polioviruses by deep sequencing [62], numerous algorithms for detection and ITD of polioviruses by various RT-PCR approaches [63][64][65][66]). We assume that upon detection of a nWPV paralytic disease cluster and initial signals from molecular testing of a common genetic signature, China would enact a containment strategy characterized by testing, contact tracing, ramping up treatment capacity, and social distancing measures in the affected block upon recognition of the infectious disease, similar to what occurred for SARS-CoV-2.…”
Section: Detection Assumptions and Intervention Scenariosmentioning
confidence: 99%